TREMATODA POLYSTOMATIDAE - CERECERO, M CRISTINA; CABALLERO Y C, EDUARDO; C, EDUARDO (Universidad Nacional Autónoma de Mexico, Escuela de Medicina, CD MEXICO, DF, MEX, 1942)
Three types of bone marrow transfusion were practiced: 1 direct, in which the donor is a healthy person; 2 crossed, in which there is exchange of material from a hyperchromic to a hypo-chromic type or vice versa, and 3 homologous, in which there is exc
ANS INST BIOL
Keywords: TREMATODA, POLYSTOMATIDAE; CIENCIAS DE LA VIDA; BIOLOGIS HUMANA; PARASITOLOGIA